Unusual case ofScedosporium apiospermumkeratitis following phacoemulsification in a systemically well patient. Issue 1 (January 2015) - Jutley, Gurjeet; Koukkoulli, Antigoni; Forbes, Jennifer; Sharma, Vikas
Abstract : N/A: We report the case of a 65‐year‐old immunocompetent woman who developed Scedosporium apiospermum keratitis after clear‐corneal phacoemulsification. A 3.5 mm by 2.7 mm full‐thickness stromal infiltrate, corresponding to the superior 2.75 mm clear‐corneal incision, was observed 44 days postoperatively. Treatment included preservative‐free voriconazole 1.0% hourly, ofloxacin 0.3% 6 times a day, oral voriconazole 200 mg once daily, natamycin 5.0% hourly, dexamethasone 0.1% 4 times a day, and ocular cyclosporine 4 times a day. After 4 months of treatment, the new vessels had regressed, the infiltrate had disappeared, and residual deep scarring remained; the uncorrected distance visual acuity was 0.8 logMAR. To our knowledge, this is the first case of S apiospermum keratitis following clear‐corneal phacoemulsification. Another unusual feature is that there were no risk factors for fungal keratitis, specifically no history of trauma, systemic illness, immunosuppression, or contact lens wear. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.